Qualitative Study of Cervical Cancer Screening Among Lesbian and Bisexual Women and Transgender Men. Issue 6 (November 2016) - Johnson, Michael J.; Nemeth, Lynne S.; Mueller, Martina; Eliason, Michele J.; Stuart, Gail W.
Abstract : Background: Lesbian, bisexual, and queer (LBQ) women, as well as transgender men, are less likely than their heterosexual and female-identifying counterparts to access cervical cancer screening services. Although numerous factors that influence receipt of cervical screening have been identified, several gaps in research and knowledge merit additional research. Objective: The aims of this study were to examine cervical cancer screening behaviors of LBQ women and transgender men using American Cancer Society guidelines as the standards for comparison and to determine factors that influence participation in cervical cancer screening. Methods: A convenience sample of 21- to 65-year-old LBQ women and transgender men was recruited from the Internet and community events. Qualitative data were collected through in-depth telephone interviews and open-ended questions on an online questionnaire. A deductive-inductive content analysis approach was used. Results: The sample was mostly non-Hispanic white women who identified as lesbian. Most were routine cervical cancer screeners. Eighteen factors/themes were identified in the data and were contextualized within a health services theoretical framework. Conclusions: This study showed that although some factors overlap with the general female population, there are other areas that are specific to LBQ women and transgender men. Creating welcoming and inclusive healthcare environments is particularly important to facilitating cervical screening among LBQ women. Implications for Practice: Nurse leaders can modify clinical environments, and clinical nurses can be educated to provide safe care for LBQ women and transgender men.